Adding Effectively to the National Resource on Art, Craft and Design: A View from a Museum Library - Watson, Rowan (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2001)
In these times of intensified resource constraints, our task is to reflect on the essential nature of our collections, to identify what makes them distinct from others, and to capitalize on that distictiveness for the benefit of all. Only then can we see how best to contribute to the collective bibliographical resource that the web begins to deliver to us in our offices and living rooms.